Pengaruh Akuntansi Manajemen Lingkungan dan Green Innovation terhadap Nilai Perusahaan di Indonesia - Melani Delia Depitasari; Bayu Rama Laksono (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
Companies play a crucial role in preserving the environment because they are the main contributors to air pollution and damage in indonesia. This study aims to analyse the effect of environmental management accounting and green innovation on firm value in indonesia. The research method used is quantitative by untilising secondary data from financial reports and sustainability reports. The research sample consist of 246 companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 period, with the sampling technique using purposive sampling method. The results showed that environmental management accounting has no effect on firm value, while green innovation is proven to have an effect on firm value.